2020
DOI: 10.1007/s40806-020-00243-z
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Perceived Neighborhood Safety and Inequality with Personality

Abstract: The relationship between neighborhood quality and personality was explored using a large nationally representative sample of midlife adults, namely, the data from the Midlife in the United States Longitudinal Study of Health and Well-Being. A multilevel approach was used to track correlations between fluctuations in perceived neighborhood safety and inequality and personality across three points in time. As predicted from life history theory, personality fluctuated along with perceived neighborhood safety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Another interesting result shows that the people-oriented trait (first-order factor 8-a mix of agreeableness, extraversion, and reliance on friends) is negatively associated with factor 20 (perceived negative quality of the neighbourhood ). Dunkel et al 41 found that higher scores in people-oriented traits (i.e. agreeableness and extraversion) are associated with higher scores in perceived positive neighbourhood qualities (such as safety) and lower scores in negative qualities such as neighbourhood inequality.…”
Section: Figure 6 Discussionmentioning
confidence: 99%
“…Another interesting result shows that the people-oriented trait (first-order factor 8-a mix of agreeableness, extraversion, and reliance on friends) is negatively associated with factor 20 (perceived negative quality of the neighbourhood ). Dunkel et al 41 found that higher scores in people-oriented traits (i.e. agreeableness and extraversion) are associated with higher scores in perceived positive neighbourhood qualities (such as safety) and lower scores in negative qualities such as neighbourhood inequality.…”
Section: Figure 6 Discussionmentioning
confidence: 99%
“…The reviewed studies most commonly used census data [ 78 , 103 , 70 ] or postcodes [ 12 , 20 , 41 , 96 ] resources for defining a neighbourhood. However, the approach of using census tracts and block-level data has been criticised since population size and spatial boundaries are not synchronous and vary according to the settlement density [ 27 , 104 ].…”
Section: Discussionmentioning
confidence: 99%